99mTc-Szintigraphie versus Farbduplex-Sonographie - Happel, C.; Truong, P. N.; Bockisch, B.; Zaplatnikov, K.; Kranert, W. T.; Korkusuz, H.; Ackermann, H.; Grünwald, F. (Nuklearmedizin - NuclearMedicine, 2013)
Since the development of colour coded duplex-sonography (ccds), several attempts have been made to implement this technique for diagnosis of focal lesions in the thyroid. There are controversial discussions on whether ccds might replace thyroid scintigraphy in diagnosis of hyperfunctional thyroid nodules. Aim of this study was the comparison of ccds and thyroid scintigraphy in diagnosis of functional thyroid autonomy. Patients, material and methods: 192 patients with thyroid nodules > 10mm detected by conventional sonography underwent thyroid scintigraphy. Additionally, these patients were subjected to ccds of the thyroid. In total, 286 thyroid nodules were examined by scintigraphy, ccds and blood tests. Results: Thyroid scintigraphy showed 67% of thyroid nodules as hyperfunctional, 19% indifferent and 14% as hypofunctional. Mean 99mTc uptake of hyperfunctional nodules was 2.19%, of indifferent nodules 1.12% and of hypofunctional nodules 1.06% respectively. The ccds allowed perinodular measurement of flow speed (hyperfunctional: 0.23 ± O.1 m/s; hypofunctional: 0.22 ± 0.1; indifferent: 0.21 ± 0.09), resistance index (hyperfunctional: 1.21 ± 1.16; hypofunctional: 0.62 ± 0.48; indifferent: 0.93 ± 1.02) and pulsatility index (hyperfunctional: 0.97 ± 0.45; hypofunctional: 0.84 ± 0.4; indifferent: 1.04 ± 0.6) in all nodules as well as intranodular measurement in some of the nodules (24% in hyperfunctional, 2% in indifferent and 15% in hypofunctional nodules). Statistic analysis of the obtained ccds data did not show any practically relevant correlations (p>0.05) with 99mTc uptake, basal TSH, fT3 or fT4. Conclusion: Thyroid scintigraphy cannot be replaced by ccds for diagnosis of functional thyroid autonomy. Reliable diagnostics still require a combination of thyroid scintigraphy, sonography and blood tests.
Keywords: Colour coded duplex-sonography; functional thyroid autonomy; scintigraphic thyroid imaging; Doppler-sonography